Proteomic and Functional Analysis Reveals Temperature-Driven Immune Evasion Strategies of Streptococcus iniae in Yellowfin Seabream (Acanthopagrus latus) - Yang, Yanjian; Zhang, Guanrong; Xu, Ruilong; Deng, Yiyang; Mo, Zequan; Li, Yanwei; Dan, Xueming (Biology (Basel, Switzerland), 2025)
Streptococcus iniae (S. iniae) is a globally significant aquatic pathogen responsible for severe economic losses in aquaculture. While the S. iniae infection often exhibits distinct seasonal patterns strongly correlated with water temperature, there is limited knowledge regarding the temperature-dependent immune evasion strategies of S. iniae. Our results demonstrated a striking temperature-dependent virulence phenotype, with significantly higher A. latus mortality rates observed at high temperature (HT, 33 °C) compared to low temperature (LT, 23 °C). Proteomic analysis revealed temperature-dependent upregulation of key virulence factors, including streptolysin S-related proteins (SagG, SagH), antioxidant-related proteins (SodA), and multiple capsular polysaccharide (cps) synthesis proteins (cpsD, cpsH, cpsL, cpsY). Flow cytometry analysis showed that HT infection significantly reduced the percentage of lymphocyte and myeloid cell populations in the head kidney leukocytes of A. latus, which was associated with elevated caspase-3/7 expression and increased apoptosis. In addition, HT infection significantly inhibited the release of reactive oxygen species (ROS) but not nitric oxide (NO) production. Using S. iniae cps-deficient mutant, Δcps, we demonstrated that the cps is essential for temperature-dependent phagocytosis resistance in S. iniae, as phagocytic activity against Δcps remained unchanged across temperatures, while NS-1 showed significantly reduced uptake at HT. These findings provide new insights into the immune evasion of S. iniae under thermal regulation, deepening our understanding of the thermal adaptation of aquatic bacterial pathogens.